MANAJEMEN KLUB WOODBALL UNIVERSITAS NEGERI SEMARANG PROVINSI JAWA TENGAH - Priagung Priagung (Universitas Majalengka, 2022)
This study aimed to describe the club's management woodball Semarang State University. This study used a qualitative descriptive approach. Techniques of collecting data using interviews, observation and documentation. The subjects of this study are coaches, administrators and athletes. The results showed: 1) Management The management of classified medium, for the purpose of achievement and excellent service to all members but do not have the administrative requirements in the form of rule by laws 2) Management Training Program Coaches and Athletes are categorized well, focus to target of the training program full responsibility and motivation. 3) Management Infrastructures categorized medium, namely the existence of alternative solutions, creative and innovative 4) Management Funding categorized as good, doing the accounting, were able to look for opportunities and use funds effectively and efficiently. Conclusions and suggestions, 1) The management considered good for that board service is further enhanced and fully responsible for the duties performed. 2) training program coaches and athletes are categorized well, the future focus more on achievement, maintained for beginners and more improved achievement 3) Management infrastructure is being classified, facilities and infrastructure officer more responsibilities and more detailed inventorying 4) Management of both categories of funding, future Unnes woodball clubs can establish cooperative relationships with sponsors who can help in terms of funding so that the club needs can be met without having to collect a fee to members.